Effects of Design Aesthetics on the Perceived Value of a Product - Shi, Aiqin; Huo, Faren; Hou, Guanhua (Frontiers in Psychology, 2021)
Design aesthetics serve a crucial role in product design. Stakeholders expect to develop highly valuable premium products by improving the design aesthetics of the products. Nevertheless, the question of how to evaluate the value of design aesthetics has not been addressed entirely. This study aimed to investigate the effects of design aesthetics on the evaluation of a product’s value by strictly controlled experiment and measured neural responses of participants. Forty participants completed a design aesthetics experiment in a laboratory setting. Pictures of products were divided as high-design aesthetics stimuli and low-design aesthetics stimuli. Both types of products were labeled with the same price. Overall, the high-design aesthetics pictures elicited smaller N100 and lower P200 amplitudes. This finding indicated that low-design aesthetics attracted more attention and high-design aesthetics triggered positive emotions. Ordinary products elicited a larger N400 value. This finding revealed the inconsistency between labeled and expected prices. The present study demonstrated that the N400 component can be used as an indicator for measuring the perceived of value of a product in a future product design study. Our findings provide ERP indicators for measuring the perceived value of a product’s design, which can be easily applied in the decision making.